Morphological description of the glans penis and baculum of Coendou quichua (Rodentia: Erethizontidae) - Leon-Alvarado, Omar Daniel; Ramírez-Chaves, Héctor E. (THERYA, 2017)
External morphology of the glans and baculum are important characters for specific delimitation, especially for rodents (Simson et al. 1995). However, for Erethizontidae there are few descriptive works; in fact, for Neotropical porcupines of the genus Coendou there is just one brief contribution for an indeterminate species by Pocock in 1922. In this work, the morphology of the glans and baculum of Coendou quichua is described. The specimen was collected at the municipality of San Vicente de Chucurí, Santander, Colombia. The penis was dissected and fixed in formaldehyde for one day, and later preserved in ethanol. The baculum was extracted and cleared with potassium hydroxide to be visualized, photographed and measured. The glans and baculum were compared with the description of others porcupines (Erethizon dorsatum and Hystrix brachyura) available in literature, and three additional Neotropical caviomorph rodents (Cuniculus paca, Dasyprocta punctata and Cavia tschudii). The glans length is almost twice the glans head width (Table 1) and comprises the third part of the total penis length. The penis presents a tenuous dark coloration on the head and small tegumentary protuberances formed by 3-4 small spines (Figure 1A). As in other hystricomorph rodents, the glans exhibits an invagination at its tip (sacculus urethralis) which has corrugated walls and presents two conspicuous spikes at the bottom (Figure 1C). Furthermore, the baculum is as large as the C. quichua glans, dorsally concave and ventrally convex (Figure 1B). Although the glans and baculum of C. quichua and E. dorsatum are similar, the latter presents larger glans (Table 1), and the sacculus urethralis lacks of corrugated walls and spiny protuberances. When comparing C. quichua and H. brachyura, the only difference is that the bottom of the sacculus urethralis, near to the spikes is smooth, without spiny protuberances. In contrast, the glans of three other Neotropical caviomorphs are remarkable different from C. quichua, where they present more complex and densely distributed tegumentary protuberances above the glans. Overall, the baculum is the most varying structure for all species, with marked differences in length and width (Table 1) and the shape of the ends. Although the family Erethizontidae is more closed related to the Cavioidea than to Hystricidae, the glans of individuals of the family Erethizontidae are more similar to the glans of the Hystricidae. In addition, for these species, both glans and baculum present important characters that might be used for taxonomic identification. However, the differences of both structures within Coendou are unknown, therefore it is necessary the description of the genitalia of additional species.